(untitled) (FULafia Journal of Science and Technology, 2023)
This work presents a simple, robust and low cost fuel level measuring system for underground liquid tanks. The major components of the system include Atmega 328P microcontroller, HC-SR04 ultrasonic sensor, Hitachi HD44780 liquid crystal display. A prototype elliptical tank was modelled and constructed using a modified gas cylinder, having its major and minor diameters and length in cm. The petrol level from the base of the tank was measured by ultrasonic sensor and converted to volumetric equivalent in litres with the aid of tank volume equation programmed into the microcontroller. Performance test was carried out on the developed system. With sensor distance, minor diameter, major diameter and length as 22, 23.39, 23.39 and 26.67 cm respectively, the tank capacity was estimated as 10 litres. The performance test showed that the system was functional and gave a mean absolute percentage error of 4.74%. The developed fuel level measuring system can be deployed for use in petrol stations, depots or other industries where information about the quantity of petrol or other fuels stored in underground tanks is required